Cardiac Inflammatory Pseudotumors in Behçet’s Disease - Bouomrani, Salem; Belgacem, Nesrine (Journal of Hypertension and Cardiology, 2019)
Introduction Cardiac non-specific inflammatory pseudotumors (NSIPT) are exceptionally associated to Behçet's disease (BD) and represent a real diagnostic and therapeutic challenge. The meaning and the mechanisms of this association are not yet well understood. The purpose of this paper is to study the epidemiologic, therapeutic, and evolutionary characteristics of cardiac NSIPT during BD Methods Systemic review of all reported cases of cardiac NSIPT associated with BD. Results We found only 6 cases of NSIPT associated with BD. Of these six patients, 4 were men (66.66%) and 2 were women (33.33%): Sex ratio =2. The average age was 26.66 years (9-35 years). The pseudotumor was unique in all cases. The chronology of occurrence of these NSIPT compared to the underlying angiitis was variable: inaugural of the disease in 4 cases, and complicating a previously known BD in 2 cases. The surgery was performed in all cases. It was carried out for diagnostic purpose in 4 cases, and therapeutic in the other 2. Additional medical treatment based on systemic corticosteroids with or without immunosuppressants was indicated in 4 patients. The evolution was favorable in 5 cases and a single case was quickly fatal. Recurrence of NSIPT was reported in one patient (20%). Conclusion The results of this review suggest a very likely association between BD and cardiac NSIPT; especially because of the scarcity of these two conditions in the general population, and the epidemiological characteristics clearly different from those of cardiac NSIPTs in the general population. The pathogenic mechanisms common to these two conditions (immune, inflammatory, reactive, and vascular) reinforce this causal link. The main differential diagnoses of these pseudotumors during BD remain cancer and intracardiac thrombosis.
Keywords: Nonspecific inflammatory pseudotumor; Behçet’s disease; Heart; Cardiac pseudotumor; Inflammation; vasculitis.